Revitalizing recovery: the impact of acute exercise on stroke survivors through a physical therapy lens - Opeyemi Adeloye; Anahita Ali; Seyi Akindolie (Academia Medicine)
Stroke is a predominant cause of long-term disability globally, frequently leading to motor, cognitive, and cardiovascular deficits that profoundly impact quality of life. Physical therapy is fundamental to stroke rehabilitation, and acute exercise therapies have demonstrated the potential to improve recovery outcomes. This review examines the effects of acute exercise on stroke survivors, emphasizing enhancements in their motor function, cardiovascular health, and neuroplasticity. A comprehensive evaluation of peer-reviewed research, encompassing randomized controlled trials, cohort studies, and case–control designs, was performed. Where the data allowed, we explored the sex-specific responses and found that the improvements were generally comparable between males (n = 780) and females (n = 546), with some studies reporting slightly greater variability in the gains in heart rate in males. Aerobic and task-specific exercises significantly boost motor function and activities of daily living, whereas resistance training improves muscle strength and reduces physical restrictions. Aerobic exercise routines produced cardiovascular benefits, including enhanced blood pressure control and heart rate variability. Moreover, neuroplastic changes, indicated by increased cortical activity and functional connectivity, suggest that acute exercise may promote brain recovery. Despite these promising results, the small sample sizes, variability in the intervention methods, and limited long-term follow-up remain challenges. Although aquatic exercise was not a primary focus of the studies included, some evidence suggests that water-based rehabilitation may improve joint mobility, reduce spasticity, and enhance balance in stroke survivors while maintaining cardiovascular stimulus. Future research should investigate how the buoyancy and resistance of water may support motor recovery and safety in acute interventions. Overall, tailored acute exercise regimens should be integrated into physical therapy to expedite the recovery and enhance the health outcomes for stroke survivors.